Pengaruh Vermicomposting Terhadap Kadar Pb Pada Biomassa Eceng Gondok (Eichhornia crassipes) - Nurfiansyah Nurfiansyah; Sulfikar; Muhammad Arham Yunus (STTI Bontang, 2023)
The presence of water hyacinth in waters can be a threat to aquatic ecosystems. Its naturally fast growth and excess nutrients in the waters cause its growth to become uncontrollable. So it is necessary to handle the biomass and produce it. One thing that can be done is to turn it into organic fertilizer. The problem is, water hyacinth is a lead (Pb) hyperaccumulator plant. So that the biomass produced by water hyacinth contains a large amount of Pb. This study aims to see the effect of vermicomposting on the amount of Pb contained in water hyacinth biomass. The research began by converting water hyacinth biomass into a living medium for earthworms. Changes in Pb levels were observed before and after the earthworms were added. The results found a change with an average initial content of 2.7857 ppm to 2.0477 ppm. So from this study, it was found that the decrease in Pb levels was 26.4924% Keywords: waterhyacinth, hyperaccumulator,biomass, earthworm, vermicomposting.